2019
DOI: 10.1590/1678-4162-11152
|View full text |Cite
|
Sign up to set email alerts
|

Cervical vertebral osteomyelitis secondary to Streptococcus equi infection in an adult horse - case report

Abstract: A 15-year-old, mixed breed, male horse was attended with a history of multiple abscesses in the cervical region with a three-year evolution. Upon admission, three fistulous tracts with drainage of purulent secretions in the cervical region, low body score, restriction of cervical movements, and painful sensitivity to palpation were observed. The horse was diagnosed with osteomyelitis secondary to Streptococcus equi infection. The initial treatment was antibiotic therapy and local curative. Owing to the lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Regarding this literary absence, it is important to acquire data for specific ultrasound technique for the examination of cervical joints and joint processes in donkeys and mules, considering the established applicability in horses (Abuja et al, 2014;Aleman et al, 2014;Alonso et al, 2019;Audigié et al, 2004;Chope, 2008;Gollob et al, 2002;Johnson et al, 2017;Mackenzie et al, 2017;Mattoon et al, 2004;Pease et al, 2012) in the diagnosis of diseases and as an aid to ultrasound-guided intra-articular punctures in these joints, whether for diagnosis or therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding this literary absence, it is important to acquire data for specific ultrasound technique for the examination of cervical joints and joint processes in donkeys and mules, considering the established applicability in horses (Abuja et al, 2014;Aleman et al, 2014;Alonso et al, 2019;Audigié et al, 2004;Chope, 2008;Gollob et al, 2002;Johnson et al, 2017;Mackenzie et al, 2017;Mattoon et al, 2004;Pease et al, 2012) in the diagnosis of diseases and as an aid to ultrasound-guided intra-articular punctures in these joints, whether for diagnosis or therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Chope (2008) reported the usefulness of performing radiography and nuclear scintigraphy, if available, prior to ultrasound examination to assist in the location and interpretation of osteoarthritis in cervical vertebral joints in horses. Also, as a diagnostic aid, ultrasound was used in the diagnosis of cervical vertebral osteomyelitis in a horse with a history of multiple cervical abscesses (Alonso et al, 2019), with the identification of areas with accumulation of secretion, in addition to certifying that there were no foreign bodies related to the injuries. Ultrasonographic examination of the cranial nuchal bursa of horses was used in (Abuja et al, 2014) to compare anatomical aspects and images obtained by magnetic resonance imaging of this structure.…”
Section: Introductionmentioning
confidence: 99%
“…VO is a well-known condition in food-producing animals and has been reported in several animal species such as cattle, sheep, goats, pigs and horses, as well as in domestic animals (Radostits et al 2006 ; Alonso et al 2019 ; Shivapour et al 2019 ; Giebels et al 2020 ; Vieira‐Pinto et al 2020). However, the traditional name in veterinary medicine for this infection is spondylitis, or discospondylitis if the intervertebral disc is affected (Moore 1992 ; Thomas 2000 ).…”
Section: Hematogenous Osteomyelitismentioning
confidence: 99%
“…VO is not frequently reported in juvenile cattle. However, some studies have reported VO in calves and foals (Alonso et al 2019 ; Lamm et al 2021 ). VO in foals often develops secondary to other conditions such as brucellosis or tuberculosis (Alonso et al 2019 ).…”
Section: Hematogenous Osteomyelitismentioning
confidence: 99%
See 1 more Smart Citation